2002
DOI: 10.1038/416701a
|View full text |Cite
|
Sign up to set email alerts
|

A mutant gibberellin-synthesis gene in rice

Abstract: The chronic food shortage that was feared after the rapid expansion of the world population in the 1960s was averted largely by the development of a high-yielding semi-dwarf variety of rice known as IR8, the so-called rice 'green revolution'. The short stature of IR8 is due to a mutation in the plant's sd1 gene, and here we identify this gene as encoding an oxidase enzyme involved in the biosynthesis of gibberellin, a plant growth hormone. Gibberellin is also implicated in green-revolution varieties of wheat, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
829
1
12

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,123 publications
(910 citation statements)
references
References 8 publications
23
829
1
12
Order By: Relevance
“…The expression of GA20ox-2 in leaves corresponded well to the semi-dwarf phenotype of the sd1 mutants. As reported previously (Sasaki et al 2002), the presence of redundant enzymes in flowers could be important for fertilization of the sd1 allele in rice breeding, since the loss-of-function of SD1 may adversely affect flower development and fertilization if SD1 were the sole gene encoding GA20ox in rice.…”
Section: Expression Analysis Of the Sd1 Genementioning
confidence: 92%
See 1 more Smart Citation
“…The expression of GA20ox-2 in leaves corresponded well to the semi-dwarf phenotype of the sd1 mutants. As reported previously (Sasaki et al 2002), the presence of redundant enzymes in flowers could be important for fertilization of the sd1 allele in rice breeding, since the loss-of-function of SD1 may adversely affect flower development and fertilization if SD1 were the sole gene encoding GA20ox in rice.…”
Section: Expression Analysis Of the Sd1 Genementioning
confidence: 92%
“…Two amplified DNA fragments were obtained; one corresponded to the previously identified GA20ox-1, and the other was a novel GA20ox gene (GA20ox-2). Mapping analysis revealed that GA20ox-2 was located on the long arm of chromosome 1, tightly linked to the sd1 locus (Sasaki et al 2002). The nucleotide (cDNA) sequence of SD1 is shown in Figure 3.…”
Section: Cloning and Molecular Characterization Of Sd1mentioning
confidence: 99%
“…The most effective QTL in increasing the shoot length via the Arroz da Terra allele, qSL1, was detected in the Chr .1 2 3 4 5 6 7 8 9 10 11 12 RM5423 RM8105 RM3233 RM2770 RM4355 RM4108 RM1248 RM1200 RM5579 RM6517 RM6467 RM3408 RM5752 RM1353 RM7479 RM8010 RM6369 RM6356 RM8018 RM1148 RM3892 RM7492 RM3882 RM7217 RM286 RM1812 et al, 2000), D10 (Arite et al, 2007), THIS1 (Liu et al, 2013), Psd1 (Li et al, 2014), CIGR (Kovi et al, 2011), SD1 (Sasaki et al, 2002;Ashikari et al, 2005. Yano et al, 2012 and SPS (Ishimaru et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Yano et al, 2012 and SPS (Ishimaru et al, 2004). Among them, SD1, which encodes for gibberellin 20 oxidase-2 (OsGA20ox2), is well known as a semi-dwarf gene (Sasaki et al, 2002). OsGA20ox2 is the enzyme involved in the biosynthesis of gibberellin (Sasaki et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation